INTERFERENSI FONOLOGI BAHASA INDONESIA PADA MASYARAKAT DAYAK BIDAYUH DI GUN TEMBAWANG, PERBATASAN INDONESIA-MALAYSIA - Lilian Slow; Puji Rahmawati (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2023)
Phonology interference is a problem in a bilingual or multilingual societies, one of them is Gun Tembawang people. Some utterances of Gun Tembawang people are incorrect in spelling certain letter. Whereas the aim of this research is to analysis phonology interference on spelling letter /s/ to be /c/ in a word cucah, /c/ to be /s/ in a word sukup, /l/ to be /r/ in a word karau, /f/ to be /p/ in a word hurup. It used a descriptive method and the kind of the research was qualitative. Moreover, it analysed by some steps, they were the data collecting, the reduction, discussing, and conclusion. The result of this research shows that the interference which happens in Gun Tembawang is dynamically, it means that the interference is temporary and by accident. It is not included in the system of Gun Tembawang dialect. Besides that, the interference happens to these couple of the letters caused by the same of wind stream blowing that is producing as the letter is connected to the next letter. For instance, the letter /s/ and /c/ are not the homogran but the interference happens when the letter /c/ is combined to /u/ in a word cucah, it will produce the wind stream blowing that same to the letter /s/ producing. The same case with the letter of /c/ and /l/. The difference matter to the interference of letter /f/. The interference caused by there is no letter /f/ in Gun Tembawang dialect so that they tend to pronounce /p/ for the words which consist of letter /f/.